Four sons of Norway. - Acker, Helen. (New York, Nelson, 1948)
The story of Ole Bull (1810-1880)--The story of Henrik Ibsen (1828-1906)--The story of Edvard Grieg (1843-1907)--The story of Fridtjof Nansen (1861-1930)--Bibliography (p. [256]) Mode of access: Internet.